Revisiting the scientific method to improve rigor and reproducibility of immunohistochemistry in reproductive science - Manuel, Sharrón L (Biol Reprod, 2018)
Immunohistochemistry (IHC) is a robust scientific tool whereby cellular components are visualized within a tissue, and this method has been and continues to be a mainstay for many reproductive biologists. IHC is highly informative if performed and interpreted correctly, but studies have shown that the general use and reporting of appropriate controls in IHC experiments is low. This omission of the scientific method can result in data that lack rigor and reproducibility. In this editorial, we highlight key concepts in IHC controls and describe an opportunity for our field to partner with the Histochemical Society to adopt their IHC guidelines broadly as researchers, authors, ad hoc reviewers, editorial board members, and editors-in-chief. Such cross-professional society interactions will ensure that we produce the highest quality data as new technologies emerge that still rely upon the foundations of classic histological and immunohistochemical principles.